2015
DOI: 10.4049/jimmunol.1500337
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 or IL-17E Protects against High-Fat Diet–Induced Hepatic Steatosis in Mice Dependent upon IL-13 Activation of STAT6

Abstract: Interleukin-25 or IL-17E is a member of IL-17 cytokine family and has immune-modulating activities. The role of IL-25 in maintaining lipid metabolic homeostasis remains unknown. We investigated the effects of exogenous IL-25 or deficiency of IL-25 on hepatic lipid accumulation. IL-25 expression was examined in paraffin-embedded tissue sections of liver from patients or in the livers from mice. Mouse model of steatosis was induced by feeding a high-fat diet (HFD). Extent of steatosis as well as expression of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 43 publications
6
42
0
Order By: Relevance
“…Furthermore, our results confirm that mice treated with IL‐25 after a HFD exhibited a polarized type‐2 immunity which is characterized by IL‐13 upregulation, promoting the development of M2 macrophages in the liver (Figure c, g) . The M2 macrophage markers, arginase I (Arg1), chitinase‐3‐like 3 (Chi3 l3 or YM‐1) and inflammatory zone 1 (FIZZ1 or Retnla), were also shown to be upregulated in IL‐25‐treated, HFD‐fed mouse livers (Figure d, g), a finding consistent with our previous studies . Moreover, CCL17, CCL22 and CCL24 expression levels were significantly upregulated (Figure e, g), while CCL1, CXCL13, CCL16 and CCL18 expression levels remained unchanged (Figure f, g).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Furthermore, our results confirm that mice treated with IL‐25 after a HFD exhibited a polarized type‐2 immunity which is characterized by IL‐13 upregulation, promoting the development of M2 macrophages in the liver (Figure c, g) . The M2 macrophage markers, arginase I (Arg1), chitinase‐3‐like 3 (Chi3 l3 or YM‐1) and inflammatory zone 1 (FIZZ1 or Retnla), were also shown to be upregulated in IL‐25‐treated, HFD‐fed mouse livers (Figure d, g), a finding consistent with our previous studies . Moreover, CCL17, CCL22 and CCL24 expression levels were significantly upregulated (Figure e, g), while CCL1, CXCL13, CCL16 and CCL18 expression levels remained unchanged (Figure f, g).…”
Section: Resultssupporting
confidence: 75%
“…Given these results, the direct application of IL‐25 in NAFLD should be approached with caution. Previous work from our laboratory demonstrates that IL‐25‐treated mice exhibit a polarized type 2 immunity characterized by an upregulation of IL‐13, leading to the development of M2 macrophages in the liver . We also found that adoptively transferred macrophages could inhibit liver and adipose tissue M1 macrophages, but this transfer does not have a direct effect on the adipose tissue or the insulin signaling (Supplementary figures 4e and 7a–e).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations